Application of metagenomic next-generation sequencing in the detection of pathogens in bronchoalveolar lavage fluid of infants with severe pneumonia after congenital heart surgery - Zheng, Yi-Rong; Lin, Shi-Hao; Chen, Yu-Kun; Cao, Hua; Chen, Qiang (Frontiers in Microbiology, 2022)
Background: Metagenomic next-generation sequencing (mNGS) has become a valuable diagnostic tool in clinical aetiology detection due to its rapidity, accuracy, and high throughput. However, the role of this technology in the diagnosis and treatment of infants with severe pneumonia after congenital heart surgery is still unclear. Methods: We conducted a retrospective cohort study of infants with severe pneumonia after congenital heart surgery. Samples were collected from infants in the hospital's cardiac intensive care unit between January 2010 and January 2022. The conventional microbiological test (CMT) group consisted of patients who underwent routine microbiological examination, and the infants' bronchoalveolar lavage fluid was examined. The mNGS group consisted of patients who underwent mNGS and routine microbiological examinations. Results: The overall positive rate of mNGS was significantly higher than that of CMT (88% vs 62.5%, P = 0.009). After receipt of the microbiological results, 30/43 (70%) patients in the mNGS group had a change in antibiotic use compared with 14/40 (35%) in the CMT group (P = 0.002). Subsequently, after adjusting the treatment plan according to the microbiological test results, the number of people with improved pulmonary infection in the mNGS group was significantly higher than that in the CMT group (63% vs 28%, P < 0.05). In addition, the duration of invasive ventilation, length of CICU stay and total hospital length of stay in the mNGS group were significantly lower than those in the CMT group (P < 0.05). Conclusion: mNGS is a valuable tool to determine the aetiology of infants with severe pneumonia after congenital heart disease surgery. It can significantly improve the sensitivity of pathogen detection, which can help target antimicrobial drugs, improve the diagnostic accuracy of the disease, and improve outcomes.